Effect of Morphologically Different Conductive Agents on the Performance of Silicon Anode in Lithium‐Ion Batteries - Madzvamuse, A.; Hamenu, L.; Mohammed, L.; Ko, J.M. (ChemistrySelect, 2018)
The performance of electrochemical electrodes, is largely dependent on the extent of efficient electrical contacts between particles, and secondly, between the current collector and the particles, amongst other factors. We report on the electrical conductivity of silicon anode electrodes that have been prepared by using conductive agents with different morphological properties. Super P® Li (SP), VGCF®‐H vapor grown carbon fibers (VGCF), and their mixture were incorporated separately into the anode electrode to observe their distinctive resultant performance. The morphological characterization was done using scanning electron microscopy whilst the electrochemical properties of the prepared electrodes were characterized by electrical resistivity test, cyclic voltammetry, charge/discharge tests and electrochemical impedance spectroscopy. The combination of VGCF®‐H and Super P® Li, results in improved performance of the anode, due to their synergistic interactions which reduce the effects encountered during the failure of the silicon anode electrode caused by large volume changes. These findings unlock new opportunities for the exploration and development of other morphologically useful conductive agents to improve silicon anode in lithium ion batteries.
Keywords: Batteries; Conductive agents; Electrical conductivity; Electrode materials; Silicon anode